PERAN PENDIDIKAN INKLUSIF DAN ENTREPRENEURIAL MINDSET DALAM PEMBENTUKAN PROSES PARENTING PADA KELUARGA PRASEJAHTERA - Jodhinata, Andreas; Dewi, Yuli Kartika; Teofilus, Teofilus; Povannes, Tyaga Adinata; Widodo, Aghnia Kamila (Jurnal Pengabdian dan Kewirausahaan, 2025)
Inclusive education has a very important role in increasing parental awareness of the importance of higher education and digital entrepreneurship, especially for students from disadvantaged backgrounds. This topic was chosen because of the low understanding of some parents who still see education only as a means of getting a job, not as a long-term investment that can improve the quality of life. Therefore, this community service program was implemented at Harapan Sejati Vocational School with the aim of educating parents about the importance of inclusive education and digital skills for their children's future. This program is implemented through various activities, such as interactive seminars, group discussions, and involving parents in digital entrepreneurship projects run by students. In this way, parents can gain insight into how inclusive education can support children's development, as well as how digital and entrepreneurial skills are very relevant in this modern era. Survey results conducted after the program showed that more than 95% of parents gained a new understanding of the value of inclusive education and the importance of digital skills. Apart from that, this program also introduces entrepreneurship as a relevant career alternative in the ever-growing digital world. Overall, this program proves that inclusive education involving parents plays an important role in student development. This also strengthens the role of parents in encouraging digital literacy and an entrepreneurial mindset, creating a young generation that is ready to compete and develop in the global era.